Perceptions of risk: A review of the effects of individual and community-level variables on perceptions of risk. (September 2013) - Hicks, Sarah; Brown, Sarah
This review consolidates the research on perceptions of risk and its antecedents to improve our understanding of the factors that influence perceptions of risk. The evidence is evaluated against the available models, theories and explanations. Online databases, relevant journals and books were searched using keywords resulting in a total of 30 papers being included in this review. It was found that the literature provided support for previous victimization, experienced both directly and vicariously, gender, race, income, perceptions of crime rates and incivilities, having a consistent effect on perceptions of risk of criminal victimization. Perceived risk was shown to have a strong influence on fear of crime, and the relationship was also found by one study to be reciprocal (Rader et al., 2007). The risk interpretation model (Ferraro, 1995) was supported by the literature but is still in need of continuing development in light of new research. The findings could be used to help reduce risk perception to a level more in line with actual risk and thus reduce fear of crime and in turn increase quality of life.